Assistance in the form of socialization and legal counseling regarding procedures for resolving land disputes (in Kuta Rayat Village, Naman Teran District, Karo Regency) - Zahara, Fatimah; Zarkawi, Ahmad Farhan (CV. Rayyan Dwi Bharata, 2024)
Land disputes are land disputes involving people, community groups, legal entities and the government. Disputed land is land whose ownership is disputed by two parties competing for ownership of the land as regulated in the regulation of the head of the Indonesian National Land Agency no. 3 of 2011. Land disputes are one of the things that often occur in rural areas, especially where we serve, namely Kuta village. Rayat, where there is no suitability or no legal involvement in resolving land disputes. The purpose of this research is to assist in community service in the form of new understanding, so that when people experience land disputes, the community can follow a resolution involving the state and law.